2020
DOI: 10.1007/s10620-020-06631-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Self-Reported Vaccination Status in a Cohort of Patients with Inflammatory Bowel Disease

Abstract: Background and Aims Prevention of vaccine-preventable diseases is important in the care of patients with inflammatory bowel disease (IBD). Thus, accurate immunization histories are critical. Many providers rely on patient self-report when assessing immunization status. The primary aim of our study was to determine the accuracy of self-reported influenza vaccination status in a cohort of patients with IBD. Methods We conducted a prospective study of patients with IBD who answered a vaccination status questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…However, the self-reported influenza vaccination status has been reported to be highly sensitive and specific in patients with IBD. 9 Finally, considering the contrasting findings of Dalal et al, 8 our results may be more representative for regions with a low incidence of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…However, the self-reported influenza vaccination status has been reported to be highly sensitive and specific in patients with IBD. 9 Finally, considering the contrasting findings of Dalal et al, 8 our results may be more representative for regions with a low incidence of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 58%
“…Importantly, several studies have found a high level of consistency between self-reported vaccine acceptance and actual vaccination rates. [42][43][44]…”
Section: Discussionmentioning
confidence: 99%
“…The WIR does not capture vaccines administered outside the state, and all Wisconsin vaccine providers are required to enter records of COVID-19 vaccine administration into the registry. 7 The WIR has been previously used to evaluate COVID-19 vaccine uptake in patients with IBD. 8 …”
Section: Methodsmentioning
confidence: 99%